Risks of seroconversion of hepatitis B, hepatitis C and human immunodeficiency viruses in children with multitransfused thalassaemia major - Lee, Way Seah; Teh, C.M.; Chan, L.L. (Wiley, 2005)
Objectives: To estimate the risks of seroconversion of hepatitis B virus (HBV), hepatitis C virus (HCV) and human immunodeficiency viruses (HIV) in children with multitransfused thalassaemia at a thalassaemic clinic in Kuala Lumpur, Malaysia. Methods: Seventy-two children (39 males, median age 11.3 years, 2.5th-97.5th centile: 1.4-19.2 years) with thalassaemia major were studied. The risks of seroconversion of HBV, HCV and HIV were estimated by comparing the seroprevalences of hepatitis B surface antigen (HBsAg), anti-HCV and anti-HIV between a defined starting point and an end point. The end point was the point when latest serological results were available while the starting point was when regular transfusion was commenced, or approximately 5 years before the end point when the duration of transfusion was longer. Results: The median duration of the study was 49 months (range 8-69 months, total 2953 patient-months). There were 2605 transfusion episodes and 4154 units of blood transfused (0.88 transfusion episode/patient per month, 1.41 units of blood transfused/patient per month). There were three new seroconversions for anti-HCV but none for HBsAg and anti-HIV. The risk of seroconversion for HCV was one in 1384 units of blood transfused (95 CI: 4000-472). The seroprevalence rates at the starting and end points were: HBsAg (1, 1), anti-HCV (10, 13) and anti-HIV (0, 0), respectively. Conclusions: The estimated risk of acquiring HCV infection in children receiving multiple blood transfusions in this study is surprisingly higher than the generally accepted estimated risk. Other routes of transmission may be important. A prospective, multicentre study to estimate such risks more precisely is needed.